Gastroesophageal reflux disease: exaggerations, evidence and clinical practice - Cristina Targa Ferreira; Elisa de Carvalho; Vera Lucia Sdepanian; Mauro Batista de Morais; Mário César Vieira; Luciana Rodrigues Silva (Brazilian Society of Pediatrics, 2014)
Objective: there are many questions and little evidence regarding the diagnosis and treatment of gastroesophageal reflux disease (GERD) in children. The association between GERD and cow's milk protein allergy (CMPA), overuse of abdominal ultrasonography for the diagnosis of GERD, and excessive pharmacological treatment, especially proton-pump inhibitors (PPIs) are some aspects that need clarification. This review aimed to establish the current scientific evidence for the diagnosis and treatment of GERD in children. Data source: a search was conducted in the MEDLINE, PubMed, LILACS, SciELO, and Cochrane Library electronic databases, using the following keywords gastroesophageal reflux; gastroesophageal reflux disease; proton-pump inhibitors; and prokinetics; in different age groups of the pediatric age range; up to May of 2013. Data synthesis: abdominal ultrasonography should not be recommended to investigate gastroesophageal reflux (GER). Simultaneous treatment of GERD and CMPA often results in unnecessary use of medication or elimination diet. There is insufficient evidence for the prescription of prokinetics to all patients with GER/GERD. There is little evidence to support acid suppression in the first year of life, to treat nonspecific symptoms suggestive of GERD. Conservative treatment has many benefits and with low cost and no side-effects. Conclusions: there have been few randomized controlled trials that assessed the management of GERD in children and no examination can be considered the gold standard for GERD diagnosis. For these reasons, there are exaggerations in the diagnosis and treatment of this disease, which need to be corrected.